Risk, Reality, Regulations? Finding what’s reasonable in copyright guidance - Lauren Byl (Journal of Copyright in Education and Librarianship)
Copyright guidance at an academic library is often provided at the nexus of the law, University policy, and the personal and professional values of the librarians and users involved in the decision making. An institution’s tolerance for risk (or lack-thereof) can create tension with librarians’ value systems. The law is often vague, leaving lots of room for differences of interpretation between University administrators, librarians, and users. Professional values, like the ones articulated by the ACRL Framework generally align with enhancing/supporting user’s rights and tend towards a copyleft point of view. Institutional risk tolerance complicates decision making further.  Higher levels of risk are generally accepted with research and teaching endeavours, directly in contrast with a lower level of risk acceptable when it comes to compliance with the law (like the Copyright Act). Lack of clarity in the law and institutional risk tolerance can be at odds with professional values, which can confuse users and undermine librarians providing guidance.